Pemanfaatan Fitur Google untuk Mendukung e-Government di Tingkat Desa/Kelurahan - Irmawati Sagala; Yudi Armansyah; Nailil Husna; Wenny Dastina (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Although the implementation of e-government in the government system in Indonesia has been running for almost decades, in practice, there are still many local government units, mainly villages and sub-districts, that encounter technical problems. The main obstacle faced by the village/sub-district government is the capacity of human resources and the availability of budgeting to support the use of information systems. Based on this issue, the Government Science Department, in collaboration with the Community Service Program (KKN) of UIN Sulthan Thaha Saifuddin Jambi students in 2021, held the e-government workshop for villages/sub-districts governments in Jambi Province with the theme